LEXICAL AND CONTEXTUAL MEANINGS IN SONG LYRICS” MOANA ORIGINAL SOUNDTRACK”: PEDAGODICAL IMPLICATION - Sudar Sudar; Tusino Tusino; Beta Radish Charica Dewi (English Review: Journal of English Education, 2023)
This research aims to analyze song lyrics containing lexical and contextual meanings in the title of “Moana Original Soundtrack.". There are three research questions such as; 1.What is the form of lexical meaning in the song lyrics? .2. What is the form of contextual meanings found in the song lyrics? 3. How is the implementation of lexical and contextual meanings for teaching purposes, particularly for teaching reading skills? Researchers used a qualitative descriptive method to conduct the study. The data sources of this research were the song lyrics of "Moana Original Soundtrack.”. Researchers’ chose five lyrics taken from internet social media. Procedures concerning to the data collection and organizations are such as; first, researchers read and comprehension of song lyrics. Second, researchers identified the words, phrases, and sentences containing lexical and contextual meaning. The third, researchers conducted coding and interpreting lexical and contextual meaning found in the song lyrics of Maona Original Soundtrck. The forth, researchers concluded the results of analysis based on findings. The results showed that there are thirty five words in the song lyrics of “Moana Original Soundtrack” contained lexical and contextual meanings. There were twelve words found in How Far I’ll Go, six words found in I am “Moana”, ten words found in Where You Are, three words found in Shiny, and four words found in Know Who You Are. Furthermore, texts of song lyrics containing lexical and contextual meaning can be use as a teaching material for critical reading skills.